"And They Shall Make War No More": Lessons about Peace‐Making and Overcoming Conflict from Colombia. (18th December 2014) - Henao Gaviria, Hector Fabio
Abstract This paper describes the background to the last fifty years of violence in Columbia and identifies its causes in inequality, poverty and displacement. It then explores the ways in which the Catholic Church has been prominent in developing processes of peace‐building that include "accompaniment" of the victims to include them in structures of citizen participation. It ends with theological and pastoral reflections on how this can be enabled practically in the Columbian context.